Cessation of thumb/finger sucking habit in children using electronic habit reminder versus palatal crib: a randomized clinical pilot study - Tassneim Eltager; Adel El Bardissy; Fatma Abdelgawad (BMC Oral Health)
Abstract Background There are different intraoral appliances for cessation of thumb/finger sucking habit, but they have many disadvantages and to overcome it, extra oral appliances with colourful and attractive shape were developed. Electronic habit reminder in the form of wristwatch with alarming sound was assessed in cessation of thumb/finger sucking habit in children versus palatal crib after 6 and 9 months. Methods This study is a randomized clinical pilot study, with allocation ratio 1:1 parallel group. Recruitment was at the diagnostic clinic, Paediatric Dentistry and Dental Public health Department, Faculty of Dentistry, Cairo University. Blinding was not feasible except for the statistician. Twenty-two children were included with age range (6–14), erupted upper first permanent molar and with thumb/finger sucking habit that resulted in open bite. After random allocation of participants into two groups: intervention group (electronic habit reminder) and control group (palatal crib), impressions were performed for fabrication of the appliances in both groups. Follow up was performed at 2 weeks, 1, 3, 6 and 9 months. Primary outcome was assessing cessation of thumb/finger sucking habit in children. Results The total number of participants who were randomized and analysed was 22 (11 per group). Cessation of thumb/finger sucking habit in the intervention group was 27.3% while in the control group was 54.5% but with no statistically significant difference (P˃0.05). Positive feedback from the parents about the useful instructions, success, and ease of using the appliances but all with no statistically significant difference (P˃0.05). Harms Regarding the palatal crib appliance, there was gingival inflammation that resolved by proper oral hygiene care. Also, interference with speech which disappeared after adaptation. Regarding appliances breakage or dislodgment, it was repaired or replaced with another one. Conclusion Although most of the parents and children accepted both appliances, cessation of the habit was higher in the control group than in the intervention group. Trial registration The trial was registered on clinicaltrials.gov, ‘Trial registration number: NCT04075617 [first submitted -29/8/2019]’.